ULTRASONOGRAPHY OF THE EXTERNAL REPRODUCTIVE ORGANS IN TOM - Ulum, Mokhamad Fakhrul; Maharani, Anizza Dyah Kartika; Kurniawan, Rizal Eko; Sariningrum, Arlita; Frastantie, Dilla; Erwin, Erwin; Tumbelaka, Ligaya ITA; Noviana, Deni (Jurnal Kedokteran Hewan, 2017)
This study aims to delineate the tissue structure of male cat external reproductive organs using ultrasound with different types of consoles and transducers frequencies through indirect method. External organ of 5 tom weighing 2-3 kg was evaluated using ultrasound with stationary console (linear transducer, 10 MHz) and portable console (linear transducer, 6.5 MHz), transcutaneously. The results showed that both console and transducer could not visualize the structure of organs sized less than 10 mm through direct method. However, the indirect method using stationary console with a 10 MHz transducer enable to visualize the organ and depicts clearly the internal organ structure such as penis and its parts, scrotum and its constituent layers, caput and cauda of epididymis, and testicles. Furthermore, portable console with 6.5 MHz transducer was still able to provide an adequate image of those organs. In general, fibrous tissues such as tunica vaginalis, tunica Dartos, funiculusspermaticus, and urethra were visible in ultrasonogram as hyperechoic structures, while soft tissues such as the parts of testicles and penis were visible as hypoechoic structures. Tissue containing fluid such as urethral lumen was visible as anechoic structure. In conclusion, indirect ultrasound imaging method was sufficient to visualize the organs sized less than 10 mm using 3-15 MHz transducer in which was currently widely used in animal health care clinics.